2015
DOI: 10.1093/cid/civ875
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Mycoplasma Species in a Patient With Septic Arthritis of the Hip and Seal Finger

Abstract: An Alaska Native hunter developed fever, swollen finger, and septic hips after harvesting seals. Evaluation of hip tissue by 16S rRNA gene polymerase chain reaction and sequencing revealed a putative novel mycoplasma species. We report the identification of this organism and describe the first known case of disseminated seal finger mycoplasmosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…KP292569) obtained from a patient with 'seal nger' and infected hip joint. He previously hunted and harvested ringed seals without protective gloves in an area where Mycoplasma infected seals were noticed before [34]. For universal detection of mycoplasmas the highly speci c and sensitive PCR assay of van Kuppenveld was used based on the conserved region of the 16S gene [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KP292569) obtained from a patient with 'seal nger' and infected hip joint. He previously hunted and harvested ringed seals without protective gloves in an area where Mycoplasma infected seals were noticed before [34]. For universal detection of mycoplasmas the highly speci c and sensitive PCR assay of van Kuppenveld was used based on the conserved region of the 16S gene [26].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, seal lice (eight batches of 15 specimens) from the grey seal were found positive for A. phagocytophilum and seal lice from three harbour seals were found positive for a single species of Mycoplasma. Comparison of partial 16S sequence indicated that the Mycoplasma species found in the seal lice pools of the habour seals was identical to a Mycoplasma isolate from an Alaska Native man who suffered from disseminated seal nger mycoplasmosis [34].…”
Section: Seal Lice and Vector-borne Pathogensmentioning
confidence: 94%
“…KP292569) obtained from a patient with 'seal nger' and infected hip joint. The patient previously hunted and harvested ringed seals (Phoca hispida) without protective gloves in an area where Mycoplasma infected seals were noticed before [31].…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of partial 16S sequence indicated that the Mycoplasma species found in the seal lice pools of the habour seals was identical to a Mycoplasma sp. from an Alaska Native hunter, who suffered from disseminated seal nger mycoplasmosis [31].…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…Transfer of bacterial pathogens by biting is not uncommon. A well-known example among people interacting with seals is the 'seal finger' (also known as sealer's finger or spekk finger), in which a seal bite to the hands becomes infected, very likely by Mycoplasma [12][13][14][15], although species like Bisgaardia have been indicated as well [16]. Also, a genetically distinct variant of Neisseria animaloris was isolated from skin abscesses, lungs and other organs of several stranded harbour porpoises with traumatic injury inflicted by grey seals [17].…”
Section: Introductionmentioning
confidence: 99%